Synthesis and study of physico-chemical properties of derivative analysis of (6-(2,6-dichlorophenyl)-3-(3-methyl-pyrazol-5-yl)-6,7-dihydro-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazin-7-yl)(r)methanone - Fedotov, S. O.; Gotsulia, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (My University, 2023)
Aim. Synthesis and investigation of properties of new (6-(2,6-dichlorophenyl)- 3-(3-methyl-1H-pyrazol-5-yl)-6,7-dihydro-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazin-7- yl)(R)methanone and study of their properties.
Keywords: тези доповідей